Utilization of Ageratum conyzoides L. as Organic Mulch for Weed Control in Sweet Corn - Ramut, Anuar; Sumoharjo, Deden; Husaini Assauwab, Muhammad; Apandi, Irfan; Barona, Rahmat; Pani, Mario; Maulia, Era; Zubir, Maulana; Untari, Yulis; Pratiwi, Vinny; Aurya Bella, Rahmi (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
Organic mulching emerges as a relevant strategy within sustainable agricultural systems.  The objective is to determine the optimal mulch dosage to suppress weeds effectively while enhancing crop growth and yield. The study was conducted within the experimental area of the Faculty of Agriculture, University Gunung Leuser, Kutacane, Aceh Province, Indonesia from September to November 2025. The experiment was arranged using a non factorial Randomized Complete Block Design comprising three treatment levels with three replications. The treatments consisted of different application rates of Ageratum conyzoides L. organic mulch, namely D0=0, D1=2, D2=4 kg m-1, which correspond to approximately 0, 20, 40 t ha-1, respectively. The variables observed included weed control percentage, ground cover, number of weed species, weed population, and fresh weed biomass. In addition, several growth parameters of sweet corn were recorded, including plant height, stem circumference, and number of leaves. Yield components measured comprised diameter, length, cob weight, kernel weight, and grain yield. The application of Ageratum conyzoides L. organic mulch at rates of 20 and 40 t ha-1 increased the percentage of weed control at 10, 20, and 30 DAP, while simultaneously reducing weed cover at 10, 20, and 30 DAP. The treatment also decreased the number of weed species at 20 and 40 DAP as well as the fresh biomass of weeds at 40 DAP. In addition, the application of Ageratum conyzoides L. organic mulch enhanced stem circumference at 30 DAP, increased the number of leaves at 10 DAP, and ultimately improved kernel yield in sweet corn.